Analisis Alasan Mendesak dalam Penetapan Dispensasi Perkawinan Anak Pada Putusan Pengadilan Cilegon Nomor 32/Pdt.P/2019/Pa.Clg - Mia Hadiati; Olivia Brilianci (UNES Law Review, 2023)
The marital dispensation provision in the latest Marriage Law adopted the ultimum remedium principle, indicating that marital dispensation is granted to parties who have not met the marriageable age limit if there are pressing conditions and no other alternatives. There are three primary factors to be considered in granting marriage dispensation, namely the protection of the child's mental state, intellectual state and parentage. This study intends to analyze the reasons for the urgency in the judge's consideration in the Cilegon District Court Decision No. 32/Pdt.P/2019/PA.CLG and understand the legal consequences of underage marriage in Indonesia. This normative research is descriptive analytical and the type of data analyzed is primary and secondary data collected through literature studies and all research data will be analyzed using qualitative methods. The results of this study indicate that the conditions that occur in the case of decision no. 32/Pdt.P/2019/PA.CLG are actually not compelling or urgent. The Cilegon District Religion Court should have considered other foundations in shar'i, juridical, sociological and health sciences of the candidates before approving the marriage dispensation of the candidates.